The Valuation of Environmental, Social, and Governance Banking: Evidence from Sri Kehati Index, Indonesia - Yohanes Mario Pratama; Elizabeth Fiesta Clara Shinta Budiyono; Mario Rosario Wisnu Aji (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to provide a fair price valuation of banking shares indexed in SRI-KEHATI as a consideration to investors, the public, and other banks regarding the long-term potential of banks that have implemented ESG. The methodology in this research uses the Discounted Cash Flow method with the Free Cashflow to Equity (FCFE) approach and the Relative Valuation method with the Price to Earnings Ratio (PER) and Price Book Value (PBV) approaches in optimistic, moderate, and pessimistic scenarios. This research focused on five banks indexed in SRI-KEHATI, projecting their fair values under three scenarios. The value of the study is in the optimistic scenario; all banks are projected to be in an undervalued position compared to prices in the capital market. In the moderate and pessimistic scenarios, the condition of the intrinsic value compared to the market value differs between banks. The results of this research can be used by investors and companies to evaluate the performance and value of green banking stocks in Indonesia listed on the SRI-KEHATI index because there is no previous research that has examined the valuation of green banking stocks within the SRI-KEHATI index in Indonesia.